Bim-technologies in Ukraine - Rebrуna P.; Nesterenko І. (Ways to Improve Construction Efficiency, 2019)
The article deals with scientific approaches to the definition of the concepts of BIM-technology, prospects of development in Ukraine, the possibilities of modeling and the connection between them. The evolution, stages of formation and prospects of development of information modeling in construction are investigated.